2006
DOI: 10.1101/gr.5346206
|View full text |Cite
|
Sign up to set email alerts
|

Origins and impact of constraints in evolution of gene families

Abstract: Recent investigations of high-throughput genomic and phenomic data have uncovered a variety of significant but relatively weak correlations between a gene’s functional and evolutionary characteristics. In particular, essential genes and genes with paralogs have a slight propensity to evolve more slowly than nonessential genes and singletons, respectively. However, given the weakness and multiplicity of these associations, their biological relevance remains uncertain. Here, we show that existence of an essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 53 publications
(49 reference statements)
3
41
0
Order By: Relevance
“…Transcription of a pseudogenised representative of the Hox gene ftz in T. tridentatus can be observed in the RT-PCR-based assays of several independent individuals (Figure 6b, Supplementary File 1). Whether other xiphosuran Hox pseudogenes are transcribed is unknown, but this example suggests the complete 'silencing' of pseudogenes may take millions of years after a WGD event, allowing sufficient time for extensive remodelling of regulatory mechanisms (Shakhnovich & Koonin, 2006). Birth and death rates for pseudogenes vary from species to species (Podlaha and Zhang, 2010) and the rates can be heightened by high neutral mutation rate, as observed in mouse (Waterston et al, 2002), or by high genomic deletion rates as seen in the fly (Petrov et al, 1996(Petrov et al, , 1998.…”
Section: Pseudogenizationmentioning
confidence: 99%
“…Transcription of a pseudogenised representative of the Hox gene ftz in T. tridentatus can be observed in the RT-PCR-based assays of several independent individuals (Figure 6b, Supplementary File 1). Whether other xiphosuran Hox pseudogenes are transcribed is unknown, but this example suggests the complete 'silencing' of pseudogenes may take millions of years after a WGD event, allowing sufficient time for extensive remodelling of regulatory mechanisms (Shakhnovich & Koonin, 2006). Birth and death rates for pseudogenes vary from species to species (Podlaha and Zhang, 2010) and the rates can be heightened by high neutral mutation rate, as observed in mouse (Waterston et al, 2002), or by high genomic deletion rates as seen in the fly (Petrov et al, 1996(Petrov et al, , 1998.…”
Section: Pseudogenizationmentioning
confidence: 99%
“…Gene duplication leads to redundancy, which relaxes selection pressure and thereby creates a substrate for functional evolution (Gu and Gu 2003;Shakhnovich and Koonin 2006;Wagner 2008). Due to redundancy, the capacity to sustain nonlethal mutations is enhanced in gene families compared to singleton genes (Clark et al 2007;Armisen et al 2008).…”
mentioning
confidence: 99%
“…One of the interesting findings presented by Shakhnovich and Koonin [34] was that paralogs that were under evolutionary pressure were able to diverge farther not only in protein sequence but also in their regulatory regions as well. The same patterns were observed in drosophila as well with a positive correlation between sequence divergence and expression [39,40].…”
Section: Co-evolution Of Proteins and Their Regulationmentioning
confidence: 99%
“…However, it was not entirely clear whether genes that were conserved for other reasons duplicated more often or if conserved genes had lower death rates and higher retention rates [38]. As a way of reconciling the two scenarios, Shakhnovich and Koonin showed that while duplication rates were largely independent of the strength of selection on the duplicates, retention of paralogs was indeed much higher for more conserved genes [34]. In the same paper, the authors show that longer retention of duplicates allows gene families under strong selection to explore more sequence space and diverge farther.…”
Section: Protein Evolution Through Duplication and Divergence -Data Dmentioning
confidence: 99%
See 1 more Smart Citation